2016
DOI: 10.1039/c6ra01966h
|View full text |Cite
|
Sign up to set email alerts
|

Curing temperature reduction and performance improvement of solution-processable hole-transporting materials for phosphorescent OLEDs by manipulation of cross-linking functionalities and core structures

Abstract: Novel solution-processable hole-transporting materials for OLEDs capable of 150 °C thermal curing could be prepared by manipulation of cross-linking functionalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 31 publications
(31 reference statements)
0
21
0
Order By: Relevance
“…Lee et al. recently reported that hole‐transporting materials with a bicarbazole core and alkoxystyrene‐based cross‐linking functionalities were thermally cross‐linked at 120 °C . Solution‐processed multilayer OLEDs using physically cross‐linking materials were first reported by Cheng and co‐workers .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al. recently reported that hole‐transporting materials with a bicarbazole core and alkoxystyrene‐based cross‐linking functionalities were thermally cross‐linked at 120 °C . Solution‐processed multilayer OLEDs using physically cross‐linking materials were first reported by Cheng and co‐workers .…”
Section: Figurementioning
confidence: 99%
“…Lee et al recently reported that hole-transporting materials with ab icarbazole core and alkoxystyrene-based cross-linking functionalities were thermally cross-linked at 120 8C. [21] Solution-processed multilayer OLEDs using physically cross-linking materialsw eref irst reported by Cheng and co-workers. [22,23] They demonstrated that uracil-functionalized poly(3-thiophene) was able to form ap hysically cross-linked layer,r esultingi n high thermals tability and excellent hole injection/transporting capabilities in the solid state.…”
mentioning
confidence: 99%
“…Organic light-emitting diodes (OLEDs) increasingly attract interest because of their great potential in the eld of highquality at panel displays and solid-state lightning. [1][2][3][4] For these applications, the luminance of OLEDs needs to reach 1000 cd m À2 (ref. [4][5][6] and even higher for the solid-state lighting devices.…”
Section: Introductionmentioning
confidence: 99%
“…BCzPh exhibits a higher glass transition temperature than CBP [ 11 , 12 ]. Bicarbazole derivatives have been studied as host materials [ 11 , 12 ], hole-transporting materials [ 13 ], and emitters [ 14 , 15 ] in thermally activated delayed fluorescent (TADF) and exciplex OLEDs. Recently, solution-processed OLEDs have attracted considerable attention due to their low-cost and non-vacuum fabrication through methods such as ink-jet printing [ 16 ].…”
Section: Introductionmentioning
confidence: 99%